The Effect of STAD with Handouts versus Direct Instruction on Nahwu Learning Outcomes of Grade VIII Students at SMP IT Al-Ishlah Maros - Suci Amalia; Muhammad Yaumi; M. Shabir U (Abjadia : International Journal of Education, 2026)
This study aims to investigate the effect of applying the Student Teams Achievement Division (STAD) cooperative learning model assisted by handouts on the nahwu learning outcomes of Grade VIII students at SMP IT Al-Ishlah Maros. It also compares the learning outcomes between students who are taught using the STAD cooperative learning model with handout assistance and those who receive direct instruction. The background of this research is based on the low nahwu learning outcomes, which are attributed to less varied teaching methods and limited instructional time. The study employed a quantitative approach with a quasi-experimental design, specifically the posttest-only control group design. The population consisted of all Grade VIII students at SMP IT Al-Ishlah Maros in the current academic year, totaling 112 students. The sample, determined through purposive sampling, comprised 42 students divided into two classes: the experimental class, which used the STAD model with handout assistance, and the control class, which used direct instruction. The research instrument was a learning achievement test in the form of multiple-choice items and sentence construction tasks. The results showed a significant difference in learning outcomes between the students taught using the STAD model with handout assistance, who achieved a higher average score of 79.17, and those taught using direct instruction, who obtained a lower average score of 42.17. This finding was confirmed by an independent t-test, which produced a t-value of 10.208 and a significance value of 0.000 < 0.05. The implications of this study indicate that the STAD cooperative learning model assisted by handouts can serve as an effective alternative to improve students’ nahwu learning outcomes. Therefore, teachers are encouraged to incorporate this model as part of their instructional strategies.